COMMUNITY-BASED HEALTH PROMOTION AND COMPLIANCE IN DIABETES MELLITUS MANAGEMENT IN INDONESIA: A CROSS-SECTIONAL STUDY - Margaretha Niken Yordana; Herman Sudiman; Yeny Sulistyowati; Rohayu Binti Hami (Journal of Public Health Research and Community Health Development, 2026)
Background: Diabetes Mellitus (DM) is a chronic metabolic disorder characterized by persistent hyperglycemia and low adherence to treatment and self-management. Purpose: This study aimed to examine the relationship between community-based health promotion programs and adherence to diabetes mellitus management in the Kodam VI/Mulawarman community, a regional command of the Indonesian National Armed Forces responsible for East Kalimantan and surrounding areas, in 2025. Methods: An analytic correlational study with a cross-sectional design was conducted among 114 patients with type 2 DM at Hesti Wira Sakti Clinic using total sampling; data were collected using structured questionnaires with Guttman and Likert scales and analyzed using univariate, bivariate (Chi-square test, α = 0.05), and multivariate (multiple logistic regression) analyses, with ethical approval obtained from Universitas Respati Indonesia. Results: Significant associations were found between participation in health education (p = 0.001; OR = 8.050), health screening (p = 0.001; OR = 6.600), and group exercise (p = 0.003; OR = 4.020) with diabetes management adherence, and multivariate analysis identified health education as the strongest predictor (Exp(B) = 6.856). Conclusion: Active involvement in community-based health promotion programs, particularly health education, is instrumental in enhancing adherence to diabetes mellitus management within the military community.